2012
DOI: 10.1021/am302053q
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in the Magnetostriction of Sintered Cobalt Ferrite by Making Self-Composites from Nanocrystalline and Bulk Powders

Abstract: Sintered polycrystalline cobalt ferrite is a potential magnetostrictive smart material for applications as sensors and actuators. A novel concept of enhancing the magnetostrictive strain of sintered cobalt ferrite by making self-composites from nanosized and bulk powders with different particle sizes of the same material as components is reported. The self-composites give higher magnetostriction coefficient and strain derivative when compared to the sintered products obtained from the individual powders. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(45 citation statements)
references
References 25 publications
5
39
0
1
Order By: Relevance
“…Electronic mail: nlebedim@iastate.edu. the previous study on samples derived from nanoparticles 6 that composite of small and large particles enhance magnetostriction amplitude. Comparing SP6 and SP8 derived from smallest particle sizes (<45 lm) and largest particle sizes (>106 lm), respectively, it is obvious that making samples with large particle size powders reduces the magnetostriction amplitude measured along the parallel direction.…”
Section: Resultsmentioning
confidence: 77%
“…Electronic mail: nlebedim@iastate.edu. the previous study on samples derived from nanoparticles 6 that composite of small and large particles enhance magnetostriction amplitude. Comparing SP6 and SP8 derived from smallest particle sizes (<45 lm) and largest particle sizes (>106 lm), respectively, it is obvious that making samples with large particle size powders reduces the magnetostriction amplitude measured along the parallel direction.…”
Section: Resultsmentioning
confidence: 77%
“…It has been experimentally shown that magnetostrictive properties of materials derived from cobalt ferrite, including the strain derivatives, are dependent on processing conditions. [25][26][27] In another study, 28 it was suggested that an enhancement of $200% in strain sensitivity may be due to non-stoichiometry which can also be related to the processing conditions. Therefore it is important to discuss the effect of Zn-substitution on the strain derivative of the samples with respect to the unsubstituted sample in the present study (i.e., x ¼ 0).…”
Section: Magnetostrictive Propertiesmentioning
confidence: 99%
“…The analysis of X-ray powder diffraction data has shown that bismuth manganite ceramics exhibit, at room temperature, two centro-symmetric phases: the BiMn 2 Recently, the novel self-composite term was introduced to describe a material, whose elemental composition is not changed, whereas the local distribution of phases varies [18][19][20]. Therefore, the Bi 12 MnO 20 -BiMn 2 O 5 compound, consisting of two stable phases, can be called a self-composite material.…”
Section: Introductionmentioning
confidence: 99%